Status Inequality, Moral Disengagement and Violence - Armin Falk (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper studies the causal effect of status differences on moral disengagement and violence. To measure violent behavior, in the experiment, a subject can inflict a painful electric shock on another subject in return for money. We exogenously vary relative status in the realm of sexual attractiveness. In three between-subject conditions, the assigned other subject is either of higher, lower or equal status. The incidence of electric shocks is substantially higher among subjects matched with higher- and lower-status others, relative to subjects matched with equal-status others. This causal evidence on the role of status inequality on violence suggests an important societal cost of economic and social inequalities.
Keywords: A13; C91; D03; Z13; 330; morality; violence; status; inequality; laboratory experiments